Development of Adjustable Static Test Equipment for Below-Knee Prosthetic Feet: A Case Study - Nurrokhim, Firmansyah Hafizh Rizal; Mawandi, Fauzan Raka; Safitri, Puspa Dinda; Mahmudah, Imam; Mirnanda, Dwiky; Adnyono, Ndaru; Lestari, Wahyu Dwi (Universitas Negeri Malang, 2025)
The high prevalence of physical disabilities in Indonesia, particularly among the productive-age population, highlights the urgent need for advancements in prosthetic technology. While local fabricators have begun producing prosthetic feet, the lack of standardized testing procedures compromises safety and performance. This study addresses that gap by developing an adjustable static testing device tailored for below-knee prosthetic feet, focusing on keel and heel tests to evaluate mechanical performance. The device includes a jig-fixture platform adjustable to 8° and 15° for heel and keel tests, respectively. It applies a 1230 N load based on AOPA standards and integrates load and displacement sensors for accurate data acquisition. Structural components are constructed from AISI 1020 steel, with fabrication involving welding, assembly, and system calibration. The testing procedure adheres to ISO 10328 to ensure reliability under realistic loading conditions. An Ottobock SACH prosthetic foot was used in trials, demonstrating the device’s ability to classify prosthetic feet into dynamic and cushioned types, based on load-bearing and energy-return characteristics. Polynomial regression analysis showed high accuracy in capturing load-displacement behavior, with R² values above 0.85 for both tests. The results offer valuable guidance for local prosthetic fabricators aiming to design testing equipment or apply AOPA and ISO standards for quality assurance. This research supports the development of a standardized testing framework for prosthetic feet in Indonesia, enhancing product safety and quality while promoting alignment with international benchmarks. The outcomes also suggest potential for broader applications in advancing prosthetic technologies and establishing national standards.